الانتهاكات الإسرائيلية بحق دور العبادة في قطاع غزة وموقف القانون الدولي الإنساني من ذلك - Alsarhi, A. A.; Muneer Ali Abdul Rab; Arif Fahmi Md Yusof (Universiti Sains Islam Malaysia, 2024)
Places of worship in Gaza Strip have been subjected to many deliberate aggressions and destructions by the Israeli occupation forces, during the three wars against Gaza. This comes in clear violation of the rules of international humanitarian law, which emphasizes protection of these places from any aggression and excluding them from the cycle of conflict, between the States. Throughout this study, the researcher highlights the violations against places of worship during the aggression on Gaza Strip and the position of international humanitarian law. The methodology used in this research is the extrapolative method. It follows the international conventions and what these conventions have approved in relation to the subject of the study. The researcher also uses the analytical descriptive approach through reading and analysis of legal texts related to armed conflicts, which are mentioned in the international conventions; in the four Geneva Conventions of 1949, in the Additional Protocols I and II in 1977, and in the literature, books and publications related to this area. In addition to the practical approach, since the study is applied to Gaza Strip. The research concluded the following: The Israeli occupation forces destroyed many places of worship during its wars on the Gaza Strip in clear violation and a flagrant violation of international conventions, particularly the Hague Convention of 1954, which confirmed its protection of such places during any aggression. The violations of places of worship during the wars against Gaza Strip constitute war crimes as affirmed by the Rome Statute. This requires prosecution of the perpetrators, bringing them to justice, holding them accountable for their crimes.